Cognitive decline profiles associated with lewy pathology in the context of Alzheimer’s disease neuropathologic change - Jon B. Toledo; David P. Salmon; Melissa J. Armstrong; Douglas Galasko (Alzheimer’s Research & Therapy)
Abstract Background Alzheimer’s disease neuropathologic change (ADNC) and Lewy pathology (LP) often coexist in cognitively impaired individuals. These pathologies’ relative distribution and severity may modify these individuals’ clinical presentation, cognitive profile, and prognosis. Therefore, we examined the contributions of LP and concomitant ADNC to disease survival and profiles of cognitive decline in preclinical and clinical stages in a large neuropathologically diagnosed group. Methods We evaluated 597 participants with LP and 491 participants with intermediate/high ADNC in the absence of LP from the National Alzheimer Coordinating Center (NACC) database. At baseline, 237 participants were cognitively normal (CN), 255 were diagnosed with mild cognitive impairment (MCI), and 596 with dementia. Cognition was assessed using three cognitive domain scores (i.e., Memory, Executive, and Language) from the NACC Uniform Dataset (UDS) neuropsychological test battery, MMSE, and Clinical Dementia Rating (CDR). Multivariate adaptive regression splines were used to evaluate associations between baseline cognitive scores and mean annual rate of change over two years. The likelihood of progression to MCI or dementia was assessed using Cox hazard models. Results Neocortical LP, independent of the clinical diagnosis, was associated with lower Executive and higher Language and Memory scores at baseline, whereas Braak V-VI neurofibrillary tangle pathology was associated with lower Memory and Language scores. Similarly, neocortical LP was associated with faster Executive decline, whereas Braak V-VI neurofibrillary tangle pathology was associated with faster Memory and Language decline. A clinical diagnosis of Lewy Body Dementia (i.e., a strong LP phenotype) was associated with the LP cognitive profile and shorter disease duration. Progression to incident MCI or dementia was primarily associated with the degree of tau pathology; neocortical LP or a diagnosis of Lewy Body Dementia only predicted progression when those with intermediate/high ADNC were excluded. Conclusions LP and ADNC differentially affected cross-sectional and longitudinal cognitive profiles in a large autopsy sample. Concomitant Braak V-VI neurofibrillary tangle pathology had a strong impact on clinical progression in those with LP, regardless of the initial stage. Thus, LB and ADNC co-pathology interact to affect cognitive domains that may be used to track Lewy Body disease longitudinally and as outcome measures in therapeutic trials.